Restorative Procedures in Colonic Crohn Disease - Martin, Sean T.; Vogel, Jon D. (Clinics in Colon and Rectal Surgery, 2013)
Surgical management for refractory Crohn colitis often involves creation of a temporary or permanent stoma. Traditionally, the procedure of choice has been a total proctocolectomy with permanent ileostomy. However, restorative procedures that help to avoid a permanent stoma are being used with more frequency. In this article, the authors will address these procedures, including colocolonic anastomosis, ileorectal anastomosis, ileal pouch rectal anastomosis, and ileal pouch anal anastomosis. Factors that may influence one's decision to perform these procedures, such as patient age and nutritional status, medical comorbidities, sphincter function, desire to avoid a permanent ostomy, and prior medical therapy, will be discussed. Functional outcomes regarding these procedures will also be described. One should keep in mind that surgery does not cure Crohn disease and that postoperative long-term management is essential in preventing progression or recurrence of disease.
Keywords: Crohn colitis; restorative surgery; ileorectal anastomosis; ileal pouch rectal anastomosis; ileal pouch anal anastomosis